2015
DOI: 10.1517/14712598.2015.1067299
|View full text |Cite
|
Sign up to set email alerts
|

Liraglutide improves carotid intima-media thickness in patients with type 2 diabetes and non-alcoholic fatty liver disease: an 8-month prospective pilot study

Abstract: Eight months of liraglutide use in patients with T2DM and NAFLD significantly reduced carotid IMT, a surrogate marker of atherosclerosis, independently of glucometabolic changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 37 publications
(8 reference statements)
0
25
0
1
Order By: Relevance
“…They are considered a second-line treatment for T2DM [33]. Apart from their glucose-lowering effect, they have further positive consequences such as cardio-protective effects [70,71] and an induction of weight loss which is very beneficial in patients with NAFLD [72].…”
Section: Glucagon-like Peptide 1 Receptor (Glp-1 R) Agonistsmentioning
confidence: 99%
“…They are considered a second-line treatment for T2DM [33]. Apart from their glucose-lowering effect, they have further positive consequences such as cardio-protective effects [70,71] and an induction of weight loss which is very beneficial in patients with NAFLD [72].…”
Section: Glucagon-like Peptide 1 Receptor (Glp-1 R) Agonistsmentioning
confidence: 99%
“…In VSMC, incretins are able to prevent vascular remodeling [4246]. Exendin-4 and GLP-1 prevent the progression of atherosclerosis in apoE −/− mice, without major effects on metabolic parameters, and markedly reduced the accumulation of monocytes/macrophages in the vascular wall [43, 45].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in Zucker fatty rats and C57BL/6 mice, exenatide caused a significant reduction in intimal hyperplasia in balloon catheter injured carotid arteries and endothelial denudation injury of the femoral artery, respectively [42, 44]. Furthermore, the GLP-1 receptor analogue liraglutide significantly reduced carotid intima-media thickness, a surrogate marker of atherosclerosis, independently of glucometabolic changes, in diabetic subjects with non-alcoholic fatty liver disease [46]. These data clearly show a direct effect of GLP-1 and its analogs on the vasculature, suggesting a therapeutical role of these peptides on vascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The trial named Liraglutide Effect and Action in Diabetes: Evaluation of Cardiovascular Outcome Results-A Long Term Evaluation (LEADER; CT. gov identifier: NCT01179048) clearly demonstrated in T2DM patients at elevated CV risk that liraglutide (1.8 mg) significantly reduces the rates of major adverse CV events [15]. In a prospective study performed on subjects with T2DM but without CAD [16], Carotid Intima-Media Thickness (CIMT) decreased independently to the well-known effects of liraglutide on both glucose and lipids [17]. Moreover, further studies demonstrated that liraglutide reduced CIMT also in subjects with metabolic syndrome, highlighting that its prevalence may be significantly reduced of about 26% in these subjects (p < 0.0001) [18].…”
Section: Glucagon Like Peptide-1 Receptor Agonists (Glp-1ras)mentioning
confidence: 99%